A case study of using eye tracking techniques to evaluate the usability of e-learning courses. (1st January 2012) - Liu, Mingzhuo; Zhu, Zhiting
Usability is an important quality indicator for interactive IT products, such as e-learning courses, and can directly impact learning effectiveness, efficiency and satisfaction. In this study, we use eye tracking method together with traditional interviewing and observing methods to evaluate and examine the functionality and usability of the homepage of an e-learning course. Through the use of eye tracking in the usability experiment, we learned finer points and developed confidence in our understanding about what drew attention, and why, on the course homepage, and by studying what people looked at and did not look at, we were able to glean more detailed insights about how the web user worked his or her way through usable and unusable designs. The integration usage of eye tracking with interviewing method produced strong corroborative results. It provided us with a richer interpretation than either technique alone. The findings from this report contribute to a broader process of iterative design and continuous development of e-learning courses or e-learning applications functionality to be effective, efficient and satisfying for students.